The Importance of Heating Unit Operations in the Food Industry to Obtain Safe and High-Quality Products - Tadini, Carmen C.; Gut, Jorge A. W. (Frontiers in Nutrition, 2022)
Civilization has begun around 3,500 BCE in Mesopotamia and the realization by people that they could manipulate food to preserve it, through sun drying, fermentation, freezing in the snow, or cooking by fire, was an important factor for the nomadic human to start settling. Food by nature is subjected to spoilage and the application of any kind of preservation method enabled storage and weighted consumption. Throughout human history, many techniques have been developed and improved such as heat treatment, drying, freezing, extraction, mixing and the use of preservatives, among others. In the food industry of the modern world, each technique is implemented through sequential steps, known as unit operations. This opinion paper presents an overview of the main heating unit operations used in the food industry, highlighting their benefits to converting raw materials into palatable products with high quality and safe for consumption. Examples are presented to illustrate how several food products available in the market were submitted only to physical transformations based on scientific knowledge. However, there is a range of intensity in physical processing and the applied energy level depends on the nature of the food, target microorganism, storage conditions, type of package, and desired shelf-life. The importance of food safety is stressed since processed foods have been criticized for confusion between nutritious values and processing steps. There are still many challenges to the food industry to design the process in optimal conditions for food quality and with less environmental impacts and novel thermal and non-thermal technologies have been studied and implemented.